Modern approaches to the treatment of joint pathology: the value of hyaluronic acid - M. M. Shamuilova; Yu. V. Sedyakina; G. Yu. Knorring (Лечащий Врач)
Pathology of the musculoskeletal system and osteoarthritis, in particular, remain a frequent reason for seeking outpatient care. Among the various joints, the knee joint is considered the most affected - it accounts for up to 25% of all lesions of the musculoskeletal system, which is associated with its supporting function and frequent traumatic injury. The growing popularity of outdoor activities, the development of playing and extreme sports leads to an increase in the frequency of injuries of the knee joint, ligamentous apparatus, as well as intra-articular injuries. It is traumatization that is recognized as one of the leading causes of subsequent osteoarthritis. The article offers brief algorithms for the diagnosis and treatment of osteoarthritis for use at the outpatient stage of medical care. Attention is paid to the use of hyaluronic acid preparations, an analysis of the literature data is carried out, the prospects for the use of such therapy in a complex of therapeutic measures are assessed. Hyaluronic acid is a natural component of synovial fluid that serves as a lubricant for articular surfaces and provides a range of protective and regulatory effects. Hyaluronic acid introduced from the outside takes on the load, replenishing the missing functions of the synovial fluid, which allows us to consider such use as prosthetics of insufficient joint function. Hyaluronic acid preparations are a fast-acting local remedy to improve the function of the affected joint and relieve pain, which is important to keep patients active. These effects are due to the rheological features of hyaluronic acid, which not only improve lubricating properties and sliding in the affected joint, but also protect the articular cartilage from shock loads. The industrially obtained hyaluronic xylote has been successfully used in the treatment of osteoarthritis for more than 30 years.